Zakat Koin Cashback E-Commerce dalam Hukum Islam - Soleha, Gladis Mar'atus; Khoiruddin; Nurkholidah, Susi (Maliyah : Jurnal Hukum Bisnis Islam, 2024)
Abstract: This study examines the potential of e-commerce cashback coins as zakat objects from an Islamic legal perspective. In the digital era, cashback is an incentive in the form of a virtual money refund after a transaction, generally in the form of coins that can be used for subsequent transactions and have a value equivalent to currency. These cashback coins have economic value and can be considered as assets owned, so it is necessary to review whether these coins meet the requirements for zakat. Using a qualitative approach through literature study, this study describes how cashback coins have the potential to become zakat objects. The results of the analysis show that cashback coins are categorized as income zakat (zakat al-mâl al mustafad). Cashback coins can be subject to zakat if they meet the criteria of nisab and full ownership (tamlik). First, cashback coins are considered full property when the user has control over their use, either for transactions or cashed out. Second, the accumulated value of cashback coins can reach a nisab equivalent to 85 grams of gold or equivalent to one-twelfth of 85 grams of gold, so a significant amount of cashback has the potential to be subject to zakat. With a zakat rate of 2.5% of the total value of the coins collected, the payment mechanism can be done monthly or annually without having to meet the haul requirements. Keywords: Cashback Coins; E-commerce; Zakat.   Abstrak: Penelitian ini mengkaji potensi koin cashback e-commerce sebagai objek zakat dalam perspektif hukum Islam. Di era digital, cashback adalah insentif berupa pengembalian uang virtual setelah transaksi, umumnya dalam bentuk koin yang dapat digunakan untuk transaksi berikutnya dan memiliki nilai setara mata uang. Koin cashback ini memiliki nilai ekonomi dan dapat dianggap sebagai harta yang dimiliki, sehingga diperlukan tinjauan apakah koin ini memenuhi syarat zakat. Dengan menggunakan pendekatan kualitatif melalui studi pustaka, penelitian ini mendeskripsikan bagaimana koin cashback berpotensi menjadi objek zakat. Hasil analisis menunjukkan bahwa koin cashback dikategorikan sebagai zakat penghasilan (zakat al-mâl al-mustafad). Koin cashback dapat dikenakan zakat apabila memenuhi kriteria nisab dan kepemilikan penuh (tamlik). Pertama, koin cashback dianggap sebagai harta milik penuh ketika pengguna memiliki kontrol atas penggunaannya, baik untuk bertransaksi atau dicairkan. Kedua, akumulasi nilai koin cashback dapat mencapai nisab yang setara dengan 85 gram emas atau setara seperduabelas dari 85 gram emas, sehingga jumlah yang signifikan dari cashback berpotensi diwajibkan zakat. Dengan kadar zakat sebesar 2,5% dari total nilai koin yang terkumpul, mekanisme pembayaran dapat dilakukan bulanan atau tahunan tanpa harus memenuhi syarat haul. Kata Kunci: E-commerce; Koin Cashback; Zakat.